ĐẶC ĐIỂM DI CƯ CỦA TRỨNG CÁ - CÁ CON THUỘC BỘ CÁ TRÍCH (CLUPEIFOMES) TẠI HẠ LƯU SÔNG HỒNG - Phạm, Hồng Phương; V.K., Nhezdoly (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
MIGRATION CHARACTERISTICS OF CLUPEIFOMES ICHTHYOPLANKTON IN THE DOWNSTREAM OF THE RED RIVER The study describes some migration charateristics of Clupeiformes ichthyoplanton in downstream of the Red river at the end of the dry season. At that time the migratory phenomenon takes place at all sampling points along 200 km downstream of the river. It is found that among the ichthyoplanton collected the Clupeifomes account for the highest percentage (62,7%) and of which 93% is eggs. The migration of Clupeiformes ichthyoplanton occurs mostly near the estuary. Its density and distribution depend on the location and time of sampling, and closely relate to the flow and tide at the downstream.